Design Of The E-KTP As a Car Security System - Novi Herawadi Sudibyo; I Gede Putra Budiartha; Bayu Nugroho (Proceeding International Conference on Information Technology and Business, 2019)
Vehicle theft cases continue to increase every year. This is very troubling vehicle users both two-wheeled vehicles or four-wheeled vehicles. The security system used today is still using analog, so it needs to be replaced using a digital system to improve the security system. The use of electronic control systems almost covers most of everyday human life. The electronic control system is practical and efficient, so many people like it. Digital electronic control systems are made to replace analog systems because they have advantages, namely practical, efficient, and more futuristic. design and construction of the use of E-KTP as a car securitysystem, this system is to ensure its security as a communication medium using SMS, to ensure the security of vehicle owner data. in conducting research the research methods used design methods. data from the study in the form of electrical and starter on / off sub system testing, short message system testing.Keywords: ArduinoNaNo, E-Ktp, Car, short message system